Pengaruh Gaya Kepemimpinan, Komunikasi, dan Motivasi Terhadap Kinerja Pada Pegawai Negeri Sipil Sekretariat DPRK Lhokseumawe - Mahendra, Yusril Riza; Sullaida, Sullaida Sullaida; Azhar, Azhar Azhar; Nurmala, Nurmala Nurmala (Department of Management Faculty of Economics and Business, UNIVERSITAS MALIKUSSALEH, 2024)
The study the influence of leadership style, communication, and motivation on the performance of civil servants of the secretariat of the Lhokseumawe City Regional Peoples Representative Council (DPRK). This study used primary data obtained by disturbuting questionnaires to 60 respondents selected using the Census Sampling technique. The data analysis method used was multiple linear regression with the help of SPSS. The results indicated that Leadership (X1) partially positively and significantly affected Performance (Y) in civil servants at the secretariat of DPRK Lhokseumawe. It indicated that good employee leadership can foster performance in communication. Communication (X2) has a positive and significant effect on performance (Y) in civil servants at the secretariat of DPRK Lhokseumawe, and Motivation (X3) had a positive and significant effect on Performance (Y) in civil servants at the secretariat of DPRK Lhokseumawe. Simultaneously, Leadership Style (X1), Communication (X2), and Motivation (X3) had a positive and significant influence on performance (Y) in civil servants at the secretariat of DPRK Lhokseumawe. Keywords : Leadership, Communication, Motivation, Performance.